Scientific Literacy and Critical Thinking Skills: A Constructivist Theory–Based Analysis in Science Learning - Asyil Arifah; Mahrus Mahrus; Diva Yuninursasih; Syahriza Maefia; Arina Ulya Asari (Indonesian Journal of Educational Innovation, 2026)
Motivated by the low level of students’ scientific literacy and critical thinking skills in science learning, which is still dominated by lecture-based methods. The study aimed to analyze the implementation of constructivist-based learning in improving students’ scientific literacy and critical thinking skills. The method used was descriptive qualitative research, with data collected through interviews, documentation, and a literature review. The research subjects consisted of science teachers from SMPN 1 Taliwang, MTsN 1 Sumbawa Barat, and SMPN 3 Taliwang. The results showed that the use of discussions, practicums, worksheets, and problem-solving activities could increase student participation, help students understand science concepts, and develop critical thinking skills through questioning, analysis, and drawing conclusions. Learning activities that relate science concepts to everyday life were also found to improve students’ scientific literacy. However, the implementation of constructivist learning still faces several challenges, such as limited instructional time, low participation among some students, and a lack of practicum tools and materials. This study contributes to the development of more active, contextual, and student-centered science learning.